Floral pigments and its cytotoxic activity: An update - Jeffrina Nancy John; Rhea Ana Mascarenhas Vijayalakshmi Gangadhara
In India, approximately 80,000 tonnes of flower waste are produced every year. The increase in floral waste has driven attention to utilise it in various fields. Flowers, with their intricate properties, are applicable in the dye, paper, incense, perfumery, and pharmaceutical industries. It can also be used for vermicomposting. The pigments extracted from temple flowers are known to show antibacterial and antifungal activity and are finding their application as anti-cancerous agents. This paper comprises an overview of the major floral pigments such as carotenoid, flavonoids and xanthophyll, which are found in temple flowers and their extraction procedures using conventional methods such as agitation, centrifugation, Soxhlet extraction and non-conventional methods such as enzymatic extraction, microwave-assisted extraction, pressurised liquid extraction and ultrasound-assisted extraction. This is followed by a brief discussion of the cytotoxic effect in vitrousing cell lines such as MCF-7, HeLa, and DU145.